Socio-Economic Factors Influencing Adoption of Low Cost Agricultural Technologies - Seema Naberia, U.S. Gautam, Aroop Kumar Gupta, (Indian Journal of Extension Education, 2022)
The study was conducted by involving 240 farmwomen (possessing small and medium landholding) under Madhya Pradesh Women in Agriculture Programme in Katni district of Madhya Pradesh. The study leads to the conclusion that the socio-economic status of small farmwomen differs from medium farmwomen. It further concludes that both the categories of beneficiaries had different level of adoption. The socio-personal attributes of the beneficiaries like age, caste, education, family type and family size, land holding, occupation, annual income, social participation were found to be positively and significantly correlated with the adoption of low cost technologies taken under MAPWA programme.